Leaving the parental home in Italy and West Germany: Opportunities and constraints. - Rusconi, Alessandra (Shaker, 2006)
This volume examines the fundamental step in the transition to adulthood: the departure from the parental home. Although this event is of crucial importance for individuals' personal development, the achievement of residential independence from parents is nowadays increasingly postponed to a later life stage. The longitudinal research presented in this book focuses, therefore, on the mechanisms that "trigger" or "discourage" the departure from the parental home in two European countries: Italy and Germany. The results of this research show that although both countries present some common developments, such as education expansion, marriage delay and decreasing births rates, these have different consequences for the leaving home behavior. Next to marriage, alternative pathways out of the parental home have gained importance in Germany, but this development cannot be observed in Italy. In this country young people still wait to leave home until they are ready to establish a new family themselves. Such diverse residential decisions can be ascribed only partially to a different value attached to the family, but rather reflect economic conditions and legal regulations that provide different opportunities and constraints for young people in the two countries.
Keywords: Sozialverhalten; Jugendlicher; Familie; Lebensbedingungen; Wohnen; Umzug; Sozialpsychologie; Sozialbeziehung; Vergleichsuntersuchung; Empirische Untersuchung; Jugendsoziologie; Junger Erwachsener; Selbständigkeit; Lebenssituation; Untersuchungsergebnis